Effectiveness of TiO2-coated stainless steel mesh reactor with UV-LED on the reduction of cigarette smoke pollutants in a closed room - Renita Dewi; Pribadi Mumpuni Adhi; Tatun Hayatun Nufus (Jurnal Polimesin, 2026)
Indoor air pollution, particularly from cigarette smoke, contains harmful Total Volatile Organic Compounds (TVOC) that poses significant health risks. This study aims to evaluate the effectiveness of a Photocatalytic Oxidation (PCO)-based air purification system utilizing a Titanium Dioxide (TiO2)-coated stainless steel mesh reactor and Ultraviolet Light Emitting Diode (UV-LED) sources at 365 nm and 390 nm wavelengths. The methodology involved synthesizing TiO2 sol and immobilizing it onto a stainless steel 304 mesh substrate via a dip-coating technique. Performance testing was conducted in a closed room (volume approx. 136 m³) where smoke from two cigarettes was introduced as the pollutant source. TVOC concentrations were monitored every 5 minutes at five distinct measurement points (center and corners) over a 2-hour period to assess spatial distribution and degradation performance. The results demonstrated that the PCO system with a 365 nm UV-LED reduced the average TVOC concentration from 0.78 ppm to 0.33 ppm, achieving a reduction rate of 57.69%. Meanwhile, the 390 nm UV-LED system decreased the concentration from 0.86 ppm to 0.32 ppm, corresponding to a 62.8% reduction. While the difference in UV-LED wavelength did not significantly alter the photocatalytic performance, light intensity and initial pollutant concentration were found to influence the degradation rate. Overall, the TiO2-coated stainless steel mesh reactor proved to be an effective solution for reducing indoor cigarette smoke pollutants.